2022
DOI: 10.3390/plants11212994
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Proline Improves Salt Tolerance of Alfalfa through Modulation of Antioxidant Capacity, Ion Homeostasis, and Proline Metabolism

Abstract: Alfalfa (Medicago sativa L.) is an important forage crop, and its productivity is severely affected by salt stress. Although proline is a compatible osmolyte that plays an important role in regulating plant abiotic stress resistance, the basic mechanism of proline requires further clarification regarding the effect of proline in mitigating the harmful effects of salinity. Here, we investigate the protective effects and regulatory mechanisms of proline on salt tolerance of alfalfa. The results show that exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…can contribute their own electrons to convert oxygen radicals into stable substances ( Deng et al., 2022 ). Exogenous proline and 4-aminobutyric acid reduce the oxidative damage of barley seedlings under aluminium and proton stress by enhancing the activities of the antioxidant enzymes SOD, POD and CAT ( Song et al., 2010 ; Guo et al., 2022 ). Acidic amino acids, including glutamic acid and aspartic acid, can act as proton donors to pair with lone pair electrons and thus exert antioxidant effects ( Zhang et al., 2016 ; Li et al., 2021 ) or enhance the antioxidant capacity by increasing antioxidant enzyme activity ( Liu and Yang, 2015 ; Fardus et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…can contribute their own electrons to convert oxygen radicals into stable substances ( Deng et al., 2022 ). Exogenous proline and 4-aminobutyric acid reduce the oxidative damage of barley seedlings under aluminium and proton stress by enhancing the activities of the antioxidant enzymes SOD, POD and CAT ( Song et al., 2010 ; Guo et al., 2022 ). Acidic amino acids, including glutamic acid and aspartic acid, can act as proton donors to pair with lone pair electrons and thus exert antioxidant effects ( Zhang et al., 2016 ; Li et al., 2021 ) or enhance the antioxidant capacity by increasing antioxidant enzyme activity ( Liu and Yang, 2015 ; Fardus et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, H 2 O 2 concentration was revealed to be inhibited in a dose-dependent manner among the NaCl concentrations. CAT, SOD, POD, and ascorbate peroxidase (APX) are the main antioxidant enzymes that scavenge excess ROS in plants [ 56 ]. SOD is regarded as the key enzyme that facilitates the catalyzing of O 2 •− to H 2 O 2 whereas CAT rapidly decomposes H 2 O 2 , producing H 2 O and O 2 [ 47 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In L. ruthenicum , P5CS activity and expression of LrP5CS1 , -2 and -3 genes were promoted under high NaCl treatments. Other scholars have reported that in hybrid glycophyte Medicago sativa , increased in P5CS activity and P5CS expression after NaCl treatment revealed an involvement of P5CS in proline biosynthesis [ 56 ]. Also, in halophyte K. virginica , it is reported that overexpression of KvP5CS1 resulted in proline hyperaccumulation [ 50 ], and the overexpression of VaP5CS and LrP5CS in some glycophyte species such as Vigna aconitifolia and Lilium regale revealed proline accumulation and consequently enhanced stress tolerance [ 50 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, studying the molecular regulation mechanism of salt tolerance in alfalfa can accelerate the development of new salt-tolerant varieties, effectively addressing the limitations imposed by soil salinization on alfalfa cultivation areas. Consequently, this will enhance the scale and level of the forage industry and play a vital role in promoting the development of circular ecological agriculture centered around forage and animal husbandry [12][13][14]. Existing research has elucidated the mechanisms underlying salt-alkali tolerance in alfalfa, focusing on areas such as seed germination, plant growth and development, physiological and biochemical reactions, and molecular biology [15].…”
Section: Introductionmentioning
confidence: 99%